Effects of Positive Hepatitis B Core Antibody and Metabolic Disorders in Hepatocellular Carcinoma in an Endemic Area of Hepatitis B Virus. (19th August 2021) - Lee, Hae Lim; Bae, Si Hyun; Lee, Jaejun; Sung, Pil Soo; Lee, Sung Won; Jang, Jeong Won; Lee, Jungmin; Choi, Jong Young; Han, Nam Ik; Yoon, Seung Kew
Background and Aims: This retrospective study aimed to investigate the impact of positive hepatitis B core antibody (anti-HBc) and metabolic disorders on clinical characteristics of hepatocellular carcinoma (HCC) patients in an HBV-endemic area. Methods: A total of 1950 consecutive patients newly diagnosed with HCC between 2002 and 2015 were included. Patient records were reviewed. We compared non-viral and non-alcoholic HCC patients with other etiological groups for HCC. In addition, we compared HCC patients with negative hepatitis B surface antigen (HBsAg) and positive anti-HBc to those with negative HBsAg and negative anti-HBc, and to those with HBV. Results: The prevalence of non-viral and non-alcoholic HCC increased from 7% in 2002–2011 to 12% in 2012–2015. The proportion of non-viral and non-alcoholic HCC gradually increased with age. Patients with non-viral and non-alcoholic HCC exhibited higher rates of metabolic disorders and preserved liver function. The rate of anti-HBc positivity was similarly high in all HCC etiological groups. The clinical features of HCC patients with negative HBsAg and positive anti-HBc were similar to those with negative HBsAg and negative anti-HBc, but significantly different from those with HBV HCC. Regarding tumor characteristics, patients in the non-viral and non-alcoholic HCC group had more advanced stages of tumors (mUICC stage III–V and BCLC stage C/D). There was no significant difference in overall survival among the patient groups. The presence of anti-HBc did not affect patient survival. Conclusion: Patients with non-viral and non-alcoholic HCC had a relatively high prevalence of metabolic disorders and preserved liver function. However, they had advanced tumor stage compared to patients from other etiological groups. Anti-HBc positivity did not affect the clinical characteristics or prognosis of non-HBV HCC patients in this study.